2015
DOI: 10.1002/ece3.1813
|View full text |Cite
|
Sign up to set email alerts
|

Determining habitat quality for species that demonstrate dynamic habitat selection

Abstract: Determining habitat quality for wildlife populations requires relating a species' habitat to its survival and reproduction. Within a season, species occurrence and density can be disconnected from measures of habitat quality when resources are highly seasonal, unpredictable over time, and patchy. Here we establish an explicit link among dynamic selection of changing resources, spatio‐temporal species distributions, and fitness for predictive abundance and occurrence models that are used for short‐term water ma… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
29
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 35 publications
(30 citation statements)
references
References 51 publications
1
29
0
Order By: Relevance
“…However, how researchers define spatial and temporal scales is important and can influence our understanding of how extreme events can directly affect organisms (Mooij et al, 2002). At fine temporal and spatial scales, resource use is highly dynamic and can vary based on the availability of other necessary resources (Mooij et al, 2002;Beerens et al, 2015), environmental conditions (Mooij et al, 2002;Hovick et al, 2014;Carroll et al, 2015a), or with biotic interactions (Ryder & Sillet, 2016). These patterns may exist at smaller scales of resolution than typically studied (Dunbar et al, 2009;Maron et al, 2015), and as a result, extreme events may facilitate changes in space use and/or survival at both fine temporal (Carroll et al, 2015a) and spatial (Hovick et al, 2014) scales.…”
Section: Introductionmentioning
confidence: 99%
“…However, how researchers define spatial and temporal scales is important and can influence our understanding of how extreme events can directly affect organisms (Mooij et al, 2002). At fine temporal and spatial scales, resource use is highly dynamic and can vary based on the availability of other necessary resources (Mooij et al, 2002;Beerens et al, 2015), environmental conditions (Mooij et al, 2002;Hovick et al, 2014;Carroll et al, 2015a), or with biotic interactions (Ryder & Sillet, 2016). These patterns may exist at smaller scales of resolution than typically studied (Dunbar et al, 2009;Maron et al, 2015), and as a result, extreme events may facilitate changes in space use and/or survival at both fine temporal (Carroll et al, 2015a) and spatial (Hovick et al, 2014) scales.…”
Section: Introductionmentioning
confidence: 99%
“…Wader distribution and evaluation modeling (WADEM) was developed to predict how wading birds respond to the changes in hydrology that will occur with Everglades ecosystem restoration (Beerens et al 2015 a , 2015 b ). It can predict Great Egret ( Ardea alba ), White Ibis ( Eudocimus albus ), and Wood Stork ( Mycteria americana ) foraging distributions across changing habitat conditions based on their selection of prey resources (defined by daily–multiannual hydrologic variables).…”
Section: Methodsmentioning
confidence: 99%
“…Research has often shown that space use can be misleading indicators of habitat quality (i.e., ecological traps; Bacon et al, 2016;Donovan & Thompson, 2001;Gates & Gysel, 1978;van Horne, 1983) because individuals may not always be able to determine habitat quality and instead rely on environmental cues to guide space use (Kristan, 2003;Storch & Frynta, 1999). Thus, determining a link between space use and demographic parameters helps ensure the predictive capabilities of using such patterns for conservation purposes (Beerens, Frederick, Noonburg, & Gawlik, 2015;Folmer & Piersma, 2012). Thus, determining a link between space use and demographic parameters helps ensure the predictive capabilities of using such patterns for conservation purposes (Beerens, Frederick, Noonburg, & Gawlik, 2015;Folmer & Piersma, 2012).…”
Section: Introductionmentioning
confidence: 99%
“…Furthermore, this relationship can be highly variable across species and vegetation communities (Bock & Jones, 2004). Thus, determining a link between space use and demographic parameters helps ensure the predictive capabilities of using such patterns for conservation purposes (Beerens, Frederick, Noonburg, & Gawlik, 2015;Folmer & Piersma, 2012).…”
Section: Introductionmentioning
confidence: 99%